Osteochondral Allograft Cartilage Transplantation for a Full-Thickness Femoral Condyle Chondral Lesion. Issue 3 (July 2019) - Wise, Kelsey L.; Ridley, Taylor J.; Macalena, Jeffrey M.
Abstract : Cartilage lesions of the knee pose a difficult challenge for orthopaedic surgeons. Osteochondral allograft transplantation is an option in the setting of large chondral or osseous defects, or after failure of other treatment options1 -3 . The use of allograft offers the benefit of utilizing both viable hyaline cartilage and bone4 . Fresh allografts are usually transplanted into the femoral condyle, although they can also be used in the patella, tibial plateau, or femoral trochlea1 . Research has shown that patients who undergo this procedure for the treatment of focal and diffuse chondral defects have favorable outcomes and satisfaction scores1 . The procedure is performed as follows. (1) Preoperative evaluation: patients are evaluated for a cartilage procedure after obtaining history, examination, and imaging (radiographs and magnetic resonance imaging). (2) Approach: a longitudinal parapatellar tendon arthrotomy is performed. (3) Debridement: the lesion is identified, and unstable cartilage is debrided back to stable cartilage. (4) Measure defect: the recipient site depth is measured in 4 positions, as on the face of a clock (12, 3, 6, and 9 o'clock). (5) Template allograft: a sizer is used to template the allograft hemicondyle. (6) Secure and harvest allograft: the allograft is secured in the Osteochondral Allograft Transplantation Surgery (OATS) Workstation (Arthrex) and harvested from cadaver bone. (7) Measure depth: the recipient depth measurements are marked on the allograft. (8) Cut graft: the graft is held with allograft-holding forceps while graft is cut with a saw. (9) Check measurements: allograft measurements are checked to ensure that they match recipient measurements. (10) Round edges: the osseous ends are rounded to assist with insertion of graft. (11) Irrigate: the allograft is irrigated after final cuts. (12) Graft insertion: the graft is inserted after lining up the 12-o'clock position recipient and donor reference marks and is held in place with a press fit. (13) Closure: standard closure in layers is performed.